Immunological evaluation of urinary trypsin inhibitors in blood and urine: Role of N- & O-linked glycoproteins - Pugia, Michael J.; Jortani, Saeed A.; Basu, Manju; Sommer, Ronald; Kuo, Hai-Hang; Murphy, Solomon; Williamson, Doug; Vranish, James; Boyle, Patrick J.; Budzinski, Danny; Valdes, Roland; Basu, Subhash C. (Glycoconjugate journal, 2007)
Urinary trypsin inhibitors (uTi) suppress serine proteases during inflammation. After liberation from proinhibitors (P-alpha-I and I-alpha-I) by the white blood cell (WBC) response, uTi readily pass through the kidneys into urine. A key uTi, bikunin, is attached to O-linked and N-linked glycoconjugates. Recently, uTi inhibitors, called uristatins, were found to lack the O-linked glycoconjugates. Monoclonal antibodies were produced using purified uristatin and screened for binding differences to uristatin, bikunin, P-alpha-I, and I-alpha-I. Antibody-binding patterns were characterized using immunoaffinity binding onto protein-chip surfaces and analysis by Surface Enhanced Laser Desorption/Ionization mass spectrometry (SELDI), using specimens from patients and from purified uTi standards. Antibodies were developed and used in an enzyme-linked immunosorbent assay (ELISA) method for uTi measurement in urine and plasma specimens. ELISA was performed on specimens from normal, presumed healthy, controls and from patients who had been screened for inflammation using a high sensitivity C-reactive protein (CRP) test and a complete blood count (CBC). Polyclonal antibody against uTi showed cross-reactivity with the Tamm-Horsfall protein (THP) and with proinhibitors. Screening of anti-uTi monoclonal antibodies (Mab) revealed antibodies that did not cross-react with either of the above, thus providing a tool to measure both uristatin and bikunin in urine with Mab 3G5 and in plasma with Mab 5D11. The monoclonal antibody 5D11 cross-reacts with specific N-linked glycoconjugates of uristatin present in plasma. In ca 96% of healthy adults, uTi were present at <12 mg/l in urine and <4 mg/l in plasma. We also found that patients with an inflammation and a CRP of >2.0 mg/l had higher urinary concentrations of uTi than the control population in every subject. Free uristatin and bikunin pass readily into urine and are primarily bound to heavy chains that constitute the proinhibitor form in plasma.